Nutritional Effect of Spices from Roasted Chicken and Beef Meat Consumption - Ekpo, A.J.; Jimmy, E.O. (Pakistan Journal of Nutrition, 2005)
The effect of chicken and beef meat paste power was determined in thirty (30) subjects; 18 males and 12 females. Of this number, 19 (63.3%) at 50% paste powder concentration had complete lysis of their red blood cells. Thirteen 13 (72.2%) males were affected by complete destruction of their red blood cells while 7 (58.3%) females were similarly affected. The assayed powder had higher concentration of magnesium and cadmium least. However, lead a poisonous substance was detected in the paste mixture. It is concluded that certain ingredients in the powder used in coating roasted chicken and beef meat taken in high concentration may lead to red blood cell destruction particularly in persons with glucose-6-phosphate dehyrogenase deficiency .